First order surface grating fiber coupler under the period chirp and apodization functions variations effects - Alsharef Mohammad; Mohammed S. Alzaidi; Mahmoud M. A. Eid; Vishal Sorathiya; Sunil Lavadiya; Shobhit K. Patel; Ahmed Nabih Zaki Rashed (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The paper has demonstrated the first order surface grating fiber coupler under the period chirp and apodization functions variations effects. The Fiber coupler transmittivity/reflectivity, the fiber coupler grating index change and the fiber coupler mesh transmission cross-section are clarified against the grating length with the quadratic/cubic root period chirp and Gaussian/uniform apodization functions. The fiber coupler delay and dispersion are simulated and demonstrated with grating wavelength with quadratic/cubic root period chirp and Gaussian/uniform apodization function. As well as the fiber coupler output pulse intensity is simulated against the time period with the quadratic/cubic root period chirp and Gaussian/uniform apodization function. The fiber coupler peak intensity variations against the transmission range variations is also demonstrated by OptiGrating simulation software.